LA RESPONSABILIDAD Y SANCIÓN PENAL EN LAS CONTRAVENCIONES DE TRÁNSITO, DEL USUARIO O ACOMPAÑANTE, QUE INCUMPLE EL DEBER OBJETIVO DE CUIDADO, AL NO USAR EL CINTURON DE SEGURIDAD - BERRÚ JIMÉNEZ, JEANS CARLOS (2019)
This thesis entitled: "THE RESPONSIBILITY AND PENAL SANCTION IN THE TRANSITIONS OF TRANSIT, OF THE USER OR ACCOMPANYING, WHICH DOES NOT FALL THE OBJECTIVE OF CARE, BY NOT USING THE SEAT BELT", makes reference to the importance of sanctioning the person who directly violates the norm of not using the safety belt, because it is common to hear the different campaigns every day, which are socialized in different means of communication, making reference to the importance of the use of the safety belt , but despite this is not fulfilled, in most traffic accidents only the driver is the one who has placed this security device, according to these aspects, it is where the importance of punishing those who break the law, but not the driver, who is only able to remember the use of the safety belt and that these devices are in optimal condition, but does not have the power to Ignoring the use of a seat belt, in many cases the occupants when seeing the requirement by the driver, place the seat belt for a moment until the inspection passes, but in the course of the trip that device is removed and do not take conscience, receiving the driver a sanction according to the provisions of the Comprehensive Organic Code Article 390 that says: Violations of fifth class traffic. - Will be punished with a fine equivalent to fifteen percent of a unified basic salary of the worker in general and reduction of four point five points in your driver's license: 10. The driver of a motor vehicle that has, according to the traffic regulations, the obligation to have safety belts and does not demand the use of it to its users or companions. The academy before this reality can not be relegated and must play an important role, because it is not correct to punish the driver of a vehicle, for the omission of a third party that fails the 5 objective duty of care by not wearing the seat belt, if sanctions the offender of said contravention correctly, this regulation would be obeyed, which has the purpose of protecting the life of all the occupants. Likewise, materials and methods were applied to develop this research, conducting interviews and surveys, which have helped me to propose a legal reform project to the Comprehensive Organic Criminal Code, in its chapter VIII, regarding traffic infractions, to guarantee the proper use of the safety belt and sanction the user or companion of the non-observance of the objective duty of care.